1993
DOI: 10.2307/1242925
|View full text |Cite
|
Sign up to set email alerts
|

Hedging Production Risk With Options

Abstract: The expected utility maximization problem is solved for producers with both price and production uncertainty who have access to both futures and options markets. Introduction of production uncertainty alters the optimal futures and options position and almost always makes it optimal for the producer to purchase put options and to underhedge on the futures market. Simulation results lend support to the practice of hedging the minimum expected yield on the futures market and hedging remaining expected production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…Lence, Sakong, and Hayes (1994) extended this model into a multiperiod framework and found an important hedging role for options. Sakong, Hayes, and Hallam (1993) also extended the model of Lapan et al (1991) by allowing for production uncertainty. They found that the optimal hedging position usually will include options, in addition to forward contracts.…”
Section: Prior Research On the Linear/ Nonlinear Instrument Choicementioning
confidence: 99%
“…Lence, Sakong, and Hayes (1994) extended this model into a multiperiod framework and found an important hedging role for options. Sakong, Hayes, and Hallam (1993) also extended the model of Lapan et al (1991) by allowing for production uncertainty. They found that the optimal hedging position usually will include options, in addition to forward contracts.…”
Section: Prior Research On the Linear/ Nonlinear Instrument Choicementioning
confidence: 99%
“…If the model incorporates basis risk and options markets in a mean-variance framework, and if the options premiums and futures prices are unbiased, then options turn out to be redundant hedging instruments; the optimal hedging strategy involves only futures (Lapan, Moschini, & Hanson, 1991). If production risk is introduced into the model, options enter the portfolio (Sakong, Hayes, & Hallam, 1993).…”
Section: Conceptual Framework Of Optimal Portfoliosmentioning
confidence: 99%
“…The specific constellation examined here refers to an example given by Sakong, Hayes, and Hallam (1993), who analyzed the hedging behavior of a corn producer in Iowa. In this…”
Section: Hedging Uncertain Cash Flows From Corn Production In Iowamentioning
confidence: 99%
“…For sales volumes not exceeding 40,000 bushels, a ϭ 0.0009 is chosen; for sales volumes ranging between 40,000 and 45,000 bushels (inclusive), a ϭ 0.00045 is chosen; and for those in excess of 45,000 bushels, a ϭ 0.00015 is chosen. Sakong et al (1993) constructed the utility function by presupposing for each subinterval an exponential utility function It is now possible to carry out a numerical examination of the scenarios. Sakong et al (1993) did so by applying a specific grid search.…”
Section: Hedging Uncertain Cash Flows From Corn Production In Iowamentioning
confidence: 99%